HP0006 A randomised controlled trial evaluating effectiveness of three hand treatment approaches in rheumatoid arthritis (ra). (1st June 2001) - Chadwick, AV; Simpson, C; Murray, K; Mulherin, D; Jones, PW; Dziedzic, K
Abstract : Background: Little evidence available about optimum therapy for the rheumatoid hand or its effect on disability. Objectives: To evaluate the effectiveness of three different therapeutic approaches to the rheumatoid hand. Methods: 67 Subjects (M = 20), mean age 59.6 yrs (range 24–77 yrs) and disease duration 13.4 yrs (range 1–52 yrs), were randomised to 3 groups. Each subject received written and verbal information about joint protection from an experienced therapist. Group 1 subjects received strengthening and mobilising exercises, Group 2 stretching exercises and Group 3 the joint protection advice alone. Subjects in Groups 1 and 2 undertook a graduated programme of increasing repetitions (up to 20) of the exercises, twice daily over the six month study period. Outcome measures were obtained by two blinded assessors at 1, 3 and 6 months using AIMS II subscales relating to upper limb, hand and finger function; dynamometry; gross and pinch grip measured using the Jamar dynamometer; the Jebson-Taylor Hand Function Test and goniometry including joint ranges for wrist, thumb and individual fingers of each hand. Ethical approval was granted from the Local Research Ethics Committee. Results: 67 patients with a confirmed diagnosis of RA entered into the study. There were no statistically significant differences in baseline characteristics or demographic data. 52 patients completed all visits for all measurements. 58 attended at their one month measurement and 54 at their 3 month measurement. 15 subjects dropped out of the study. There was no significant difference in drop out rates between the 3 groups. One subject was lost to follow up. Analysis was performed using the SPSS package version 10.0. Differences in change between baseline and follow-up at 6 months were assessed using ANOVA for approximately normal data and Kruskal-Wallis test for non-normal data. At 6 months there was a statistically significant difference in AIMS II Upper limb function (p = 0.007, F-ratio 5.47) in the 3 groups. Comparison of pairs of groups at the 5% level of significance with Bonferroni adjustment showed that Group 1 was significantly different from Groups 2 and 3. In addition there were non-significant differences but improvements noted in AIMS (hand and finger function subscales) and pinch grip for both hands in this group. There were no changes in hand function or impairment measures in Groups 2 or 3. Conclusions: This study demonstrates a statistically and clinically significant improvement in upper limb function following a programme of home strengthening hand exercises in patients with RA. Further work is recommended to evaluate which specific exercises are most beneficial.